Gebed en die vorming van Christelike identiteit in Openbaring - Koester, Craig R. (HTS teologiese studies, 2015)
Prayer and the formation of Christian identity in Revelation. The use of prayer in the book of Revelation is analysed. It is illustrated that heavenly prayer is directed to God, but that Jesus is also the subject of praise in contexts of prayer. Specific attention is given to the relation between prayer and Christian identity, illustrating how prayer serves the formation and sustenance of the Christian community within this world. Prayer also aims at witnessing to this world, thus strengthening Christian identity. Prayer further has a strong eschatological dimension, calling for the return of the Lord Jesus.